College athletes' perceptions of coaching behavious: differences between indiviual and team sports - Aleksic-Veljkovic, A.; Djurovic, D.; Dimic, I.; Mujanovic, R.; Zivcic-Markovic, K. (Baltic Journal of Sport and Health Sciences, 2016)
Background. The aim of this research was to examine differences between athletes` perception of coaching behaviors in individual and team sports. Methods. College athletes (N = 100) participated in the study. Three questionnaires were administered to the athletes: Demographic questionnaire, Leadership Scale for Sports and Negative Coaching Behavior Questionnaire. Results. The results of this study revealed the significant differences among athletes` perception of coaching behaviors in individual and team sports. Individual athletes in this study gave higher ratings to training and instruction, social support and positive feedback leader behavior from their coaches. Also, athletes from individual sports had smaller scores on two dimensions and total score of negative coaching behavior questionnaire. Conclusion. Those findings suggest that the behavior of the coach directed towards improving the performance of athletes` was higher evaluated from athletes in individual sports. Further studies should provide more information about coaches` behavior during the competitive.